Convection in rotating non-uniformly stratiﬁed spherical ﬂuid shells: a systematic parameter study - ŠIMKANIN, Ján; HEJDA, Pavel; JANKOVIČOVÁ, Dana (Contributions to Geophysics and Geodesy, 2009)
A systematic parameter study of rotating convection in non-uniformly stratiﬁed spherical shells in dependence on the Prandtl number, Ekman number and Rayleigh number is presented. Attention is focused on the case, in which the thickness of both sublayers (stable and unstable) is the same (which was not investigated before). In our case the convection is not suppressed in the stably stratiﬁed region but, it is developed in both sublayers. Cases of small and large Prandtl numbers are characterized by the creation of multilayer convective structures. Convective motions take place simultaneously in the stable and unstable layers and form a multilayer structure. On the other hand, it is not possible to observe any multilayer convection for Prandtl number equal to one but it is possible to observe the small-scale structures. A conclusion is that our case is similar to the case in which the thickness of unstable sublayer is greater than that of stable one.